Monetary policy strategies to navigate post-pandemic inflation: An assessment using the ECB's New Area-Wide Model - Matthieu Darracq Pariès; Antoine Kornprobst; Romanos Priftis (European Central Bank (ECB), 2024)
We evaluate how the euro area economy would have performed since mid-2021 under alternative monetary policy strategies. We use the ECB's workhorse estimated DSGE model and contrast actual policy conduct against alternative strategies which differ in their "lower-for-longer" commitment as well as policymaker preferences regarding inflation and output volatility. Assuming that the monetary authority had full knowledge of prevailing conditions from mid-2021 onwards, the alternative policy strategies would call for anticipated timing of the start of the hiking cycle: earlier tightening would prevent inflation from peaking at 10%, but the forceful tightening since 2022:Q3 prevented higher inflation from becoming entrenched. However, once evaluating monetary policy on real-time quarterly vintages of incoming data and projections, the alternative interest rate paths would be broadly consistent with the observed policy conduct. The proximity of some benchmark optimal policy counterfactuals with the baseline, brings further indication that the actual policy conduct succeeded in implementing an efficient management of the output-inflation trade-off.
Keywords: C53; E31; E42; E52; E58; 330; estimated DSGE model; monetary policy frameworks; optimal policy; dual mandate; euro area